ORGANIZATIONAL CULTURE, TRAINING AND WORK EXPENSES ON THE PERFORMANCE EMPLOYEES OF PT SUNWOO GARMENT INDONESIA - Evi Oktaviani; Sudarwati Sudarwati; Siti Maryam (International Journal of Economics, Business and Accounting Research (IJEBAR), 2020)
This study aims to determine the effect simultaneouslyi (simultaneously) and partiallyi organizationali culture variablesi, training and workloadi on the performance of the employeesi of PT Sunwoo Garmenti Indonesia. Thisi study usesi quantitative researchi, the populationi in this study is part of the employees of PT Sunwoo Garmenti Indonesia, amountingito 100 people. Data collection techniquesi in this studyiare 1) observation, 2) interview, 3) questionnaire, 4) literature study. This studyi uses statisticali data analysisi techniquesi with version 25 for Windows program. T testi resultsi state that organizationali culture and trainingi variables have a positive and significanti effect on employee performance, while the workloadi variable has a negative and significantieffect on employee performance. F Testi results state that the variablesi of organizationali culture, training and workloadi simultaneously have a significantieffect on employee performance. Resultsi of the Determinationi Coefficient Analysis (R2) is obtainediresults of 0.563 or 56.3%. This meansi that organizationali culture, trainingi and workloadi variables are able to get an effecti of 56.3% on the improvementi of the performance of the employeesi of PT Sunwoo Garment Indonesia. Keywords: organizational learning, training, workload and employee performance.